Management accounting principles - Aseervatham, Al.; Anandarajah, D. (Melbourne, VIC : Nelson, 1996)
This book is about: Management accounting concepts; manufacturing statements; The cost cycle; Prime cost; ...
Keywords: Accounting; Economics; Business; Managerial accounting; Cost accounting